Students' Reading Comprehension of Descriptive Text Utilizing the SQ4R Method in Grade X at SMA Negeri 1 Batang Toru - Sandi Yogi Saputra; Rahmat Huda; Happy Sri Rezeki Purba; Khairunnisah; Yasmin Cantika Khairunnisa Daulay; Feri Gunawan; Ufi Ruhama; Owanwa Khari (CV. Alfa Pustaka, 2025)
This study is prompted by the inadequate reading interest and comprehension of grade X students at SMA Negeri 1 Batang Toru regarding descriptive texts in English. The primary issues found encompass insufficient student engagement in reading, challenges in comprehending language and text content, and a restricted application of appropriate instructional tactics by the educator. The objective of this research is to evaluate the efficacy of the SQ4R method (Survey, Question, Read, Recite, Review, Reflect) in enhancing students' reading comprehension of descriptive texts. The study utilizes a quantitative methodology featuring a pre-test and post-test framework. The population comprises all Grade X students at SMA Negeri 1 Batang Toru for the 2024/2025 academic year, with the total number are 251 students. The researcher employed purposive sampling to pick grade X6 as the sample, which initially comprised 35 students; however, only 19 participated in the study. The primary data comprises reading comprehension test scores obtained prior to and subsequent to the application of the SQ4R approach. The data collection equipment comprised a reading test and questionnaires. The data analysis methods employed included descriptive statistical analysis and t-tests to assess the significance of differences between pre-test and post-test outcomes. The students' reading proficiency was commendable, and the study indicated an enhancement in the average reading comprehension score from 72.37 in the pre-test to 87.63 in the post-test following the implementation of the SQ4R approach, resulting in an elevation of students' reading ability to an excellent level. In conclusion, the SQ4R method demonstrated efficacy in improving students' reading comprehension of descriptive texts and is advocated as an alternate instructional strategy for reading in senior high schools.